(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article is devoted to the formation of a healthy lifestyle culture among future physical education teachers, the development of physical qualities, the formation of skills of biological, mental, physical condition and work activity, compliance with hygienic rules in education and upbringing.